Ferrocene‐Functionalized Multiwalled Carbon Nanotubes for the Simultaneous Determination of Dopamine, Uric Acid, and Xanthine. Issue 3 (13th December 2021) - Wang, Junyan; Khorasani Motlagh, Mozhgan; Noroozifar, Meissam; Kerman, Kagan; Kraatz, Heinz‐Bernhard
Abstract: In this proof‐of‐concept study, ferrocene‐modified multiwalled carbon nanotubes (Fc‐MWCNT) were synthesized by amide coupling and the resulting product was characterized by transmission electron microscopy and Fourier‐transform infrared spectroscopy. The Fc‐MWCNT were used in a graphite paste electrode (GPE) for the highly sensitive simultaneous determination of dopamine (DA), uric acid (UA), xanthine (XA) by differential pulse voltammetry. The sensor displayed a linear range up to 4.5, 14, and 82.0 μM with a limit of detection of 2.0, 10.0 and 5 nM for DA, UA, and XA, respectively. In addition, the modified GPE/Fc‐MWCNT displayed a high stability, reproducibility, and repeatability. The GPE/Fc‐MWCNT was used for simultaneous determination of DA, UA, and XA in two different real samples with a recovery rate of 95–104 %. Abstract : Ferrocene‐modified multiwalled carbon nanotubes (Fc‐MWCNT) were synthesized by amide coupling. The Fc‐MWCNT were used for the highly sensitive simultaneous determination of dopamine (DA), uric acid (UA), xanthine (XA) by DPV. The sensor displayed a linear range up to 4.5, 14, and 82.0 μM with a limit of detection of 2.0, 10.0 and 5 nM for DA, UA, and XA, respectively.